Modification Of The SERVQUAL Model With Sharia Compliance Dimension In The Digital Services Of Indonesian Islamic Bank - Irmadatus Sholekhah; Dibyo Waskito Guntoro; Ahmad Alwi (Universitas Islam Darul 'ulum Lamongan, 2026)
The digital transformation in the Islamic banking industry presents a unique challenge: harmonizing technological convenience with compliance with Sharia principles. This study aims to test a modified SERVQUAL model by incorporating the Sharia Compliance dimension in assessing the digital service quality of Bank Syariah Indonesia (BSI). A quantitative approach was employed involving 50 active BSI customers in Jember Regency, selected through random sampling. Data were collected using a Likert-scale questionnaire (1–4) and analyzed using multiple linear regression with IBM SPSS 21. Validity and reliability tests indicated that the research instrument fell into the excellent category, with Cronbach's Alpha values exceeding 0.9 for all variables. The main findings reveal that the Sharia Compliance dimension exerts a significant influence on service quality, with an effective contribution of 58.2 percent. In contrast, customer loyalty had no significant effect, accounting for only 5.76 percent. Simultaneously, both variables explained 64 percent of the variation in service quality.